The Entrepreneurship Curriculum Development and Implementation from Tarumanegara University to Students of SMK Triguna, South Jakarta, Indonesia - Lina Gozali; Evera Olivia; Jennifer Juyanto; Laurencia Tiffany; Vanecia Marchella Hardinanerl; Meiluseano Bramnas Hede; Fithri Mawartini (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2022)
It is essential in obtaining and developing a business so as to increase company profits to ensure the sustainability of the next business world. Business is usually identified with obtaining the maximum profit or as much as possible so as to be able to continue to develop the business world that is occupied. The concept of selling itself is not only focused on selling goods and services. The new concept emphasized the ability of business actors to meet consumer needs so that they can achieve a good level of customer satisfaction. Therefore, it takes the ability, knowledge, motivation, confidence, and skills needed to achieve the goals of the business world. The educational model was chosen during the implementation of Inquiry Learning and Problem Based Learning. The students were carried out in 1 hour 15 minutes to understand the mathematical model of the business world forecasting, and there were games and questions and answers. Management skills should also be obtained from mathematical analysis of a simple framework or problem. From this introduction to consumer needs, a conclusion can be drawn to understand existing customer demand patterns. This can develop business startups to capture patterns of customer demand in meeting customer satisfaction.